Implementasi Metode Al Miftah Lil Ulum Dalam Membaca Kitab Fathul Qorib Bagi Pemula Di Pondok Pesantren Sidogiri Salafi Kabupaten Pasuruan - Maulana Restu; Siti Wahyuni (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
Islamic education in Indonesia, the majority is rooted in the education model of an Islamic boarding school. In the world of pesantren, the position of the yellow book is very strategic because the yellow book is the book references and the curriculum in the education system. Nahwu and Shorrof are the initial keys to mastering the yellow book, but the problem is, many students, especially early childhood students and beginners, they find it difficult to learn Nahwu and Shorof, while the two fans are the key to being able to read the yellow book. with 3 (three) data collection techniques, namely; observation, interview and documentation. The analysis technique in this research is to use qualitative data analysis consisting of 1) data reduction; 2) data presentation, and 3) conclusions, where the process took place circularly during the study. The results showed that the preparation of the method was based on the unrest that occurred in the Sidogiri Islamic Boarding School and the Al-Miftah Lil ‘Ulum method in the Sidogiri Islamic Boarding School well organized, both internally and externally.